The Influence of Modernization on the Formation of Legislation in Indonesia - Y. Edo Budi Prasetyo; Cokorde Istri Dian Laksmi Dewi; Benyamin Tungga (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract The existence of laws and regulations in Indonesia reflects the principle of popular sovereignty, realized through a democratic legislative process, stipulated in Law No. 12 of 2011 and organized through the systematic National Legislation Program (Prolegnas) based on scientific studies through Academic Papers. This process involves synergy between the House of Representatives (DPR), the Government, and the Regional Representatives Council (DPD) in deliberative debates aimed at producing quality laws. However, globalization brings challenges in the form of harmonizing national law with international standards, the involvement of non-state actors, and human rights and environmental issues. Therefore, the legal system must adapt to remain responsive and oriented towards the values of Pancasila and local wisdom as the nation's identity in facing global dynamics. This research aims to provide an in-depth analysis. Using a descriptive-analytical approach, this study is expected to provide a comprehensive overview of the legal and regulatory challenges faced. Keywords: Legislation, Globalization, Sovereignty